Limitations of acoustic monitoring at wind turbines to evaluate fatality risk of bats. (24th March 2021) - Voigt, Christian C.; Russo, Danilo; Runkel, Volker; Goerlitz, Holger R.
Abstract: Wind turbines (WTs) frequently kill bats worldwide. During environmental impact assessments, consultant ecologists often use automated ultrasonic detectors (AUDs) to estimate the activity and identity of bats in the zone of highest mortality risk at WTs in order to formulate mitigation schemes, such as increased curtailment speeds to prevent casualties. While acknowledging the potential of acoustic monitoring, we evaluate the limitations of AUDs for monitoring bats at WTs and highlight directions for future research. We show that geometric attenuation and atmospheric attenuation of ultrasonic echolocation calls, in conjunction with limited sensitivity of ultrasonic microphones, severely constrain detection distances of bats at WTs. Taking into account the acoustic shadow produced by the nacelle, AUDs cover only approximately 23% of the risk zone for a bat calling at 20 kHz and 4% for a bat calling at 40 kHz, assuming a 60 m blade length. This percentage will further decrease with increasing blade lengths in modern WTs. Additionally, the directionality of echolocation calls and the dynamic flight behaviour of bats constrain the detectability of bats. If a call can be detected, the low interspecific and high intraspecific variation of echolocation call characteristics may impair species identification, limiting the power to predict population‐level effects of fatalities. We conclude that technical, physical, and biological factors severely constrain acoustic monitoring in its current form. We suggest the use of several AUDs, installed at complementary sites at WTs, and the testing of other techniques, such as radar, cameras, and thermal imaging, to inform stakeholders on the mortality risk of bats at WTs. Abstract : Automatic ultrasonic detectors (AUD) help to estimate the acoustic activity of bats in the risk zone of wind turbines, but physical processes such as geometric and atmospheric attenuation and technical limitations may reduce the probability of recording bats and of identifying species correctly, indicating that the current application of AUD at wind turbines is severly impaired; particularly at large turbines.